Cat‐scratch disease: ocular manifestations and treatment outcome. Issue 4 (5th March 2018) - Habot‐Wilner, Zohar; Trivizki, Omer; Goldstein, Michaella; Kesler, Anat; Shulman, Shiri; Horowitz, Josepha; Amer, Radgonde; David, Ran; Ben‐Arie‐Weintrob, Yael; Bakshi, Erez; Almog, Yehoshua; Sartani, Gil; et al.
Abstract: Purpose: To characterize cat‐scratch disease (CSD) ocular manifestations and visual outcome and evaluate the effect of systemic antibiotics and corticosteroids on final visual acuity (VA). Methods: Multicentre retrospective cohort study. Medical records of 86 patients with ocular disease (107 eyes) of 3222 patients identified in a national CSD surveillance study were reviewed. Results: Mean age was 35.1 ± 14.2 years. Median follow‐up was 20 weeks (range 1–806 weeks). Of 94/107 (88%) eyes with swollen disc, 60 (64%) had neuroretinitis at presentation, 14 (15%) developed neuroretinitis during follow‐up, and 20 (21%) were diagnosed with inflammatory disc oedema. Optic nerve head lesion, uveitis, optic neuropathy and retinal vessel occlusion were found in 43 (40%), 38 (36%), 34 (33%) and 8 (7%) eyes, respectively. Good VA (better than 20/40), moderate vision loss (20/40–20/200) and severe vision loss (worse than 20/200) were found in 26/79 (33%), 35/79 (44%) and 18/79 (23%) eyes at baseline and in 63/79 (80%), 11/79 (14%) and 5/79 (6%) eyes at final follow‐up, respectively (p < 0.001). Significant VA improvement (defined as improvement of ≥3 Snellen lines at final follow‐up compared to baseline) occurred in 12/24 (50%) eyes treated with antibiotics compared with 14/16 (88%) eyes treated with antibiotics and corticosteroids (p = 0.02). Multivariate logistic regression was suggestive of the same association (odds ratio 7.0; 95% CI 1.3–37.7; p = 0.024). Conclusion: Optic nerve head lesion is a common and unique manifestation of ocular CSD. Most patients improved and had final good VA. Combined antibiotics and corticosteroid treatment was associated with a better visual outcome.